Complications and comorbidities associated with antineoplastic chemotherapy: Rethinking drug design and delivery for anticancer therapy - Xiaoman Mao; Shuang Wu; Dandan Huang; Chong Li (Elsevier, 2024)
Despite the considerable advancements in chemotherapy as a cornerstone modality in cancer treatment, the prevalence of complications and pre-existing diseases is on the rise among cancer patients along with prolonged survival and aging population. The relationships between these disorders and cancer are intricate, bearing significant influence on the survival and quality of life of individuals with cancer and presenting challenges for the prognosis and outcomes of malignancies. Herein, we review the prevailing complications and comorbidities that often accompany chemotherapy and summarize the lessons to learn from inadequate research and management of this scenario, with an emphasis on possible strategies for reducing potential complications and alleviating comorbidities, as well as an overview of current preclinical cancer models and practical advice for establishing bio-faithful preclinical models in such complex context.